Enormous enhancement of molecular ionization at high x-ray intensity. Issue 15 (January 2020) - Inhester, L; Hao, Y; Son, S-K; Santra, R
Synopsis: The ultra-intense and ultra-short x-ray pulses provided by X-ray Free-Electron Lasers (XFELs) sequentially ionize molecular samples many times. In this context, we have recently discovered that under intense x-ray radiation the total charge of a molecule is enhanced compared to the sum of charges of its constituent isolated atoms[2, 3]. We report here on new theoretical results[5] for iodobenzene (C6 H5 I) that show an even stronger ionization enhancement than previously observed for iodomethane (CH3 I)[3].